'Make Classical Music Great Again': Contemporary Music, Masculinity, and Virality in Memetic Media in Online Spaces. Issue 4 (4th July 2022) - Freitas, Joana
Abstract : While an image may be worth a thousand words, a meme can be worth much more. From politics to videos, games to social media, memes are an integral part of today's online communication and content production in the paradigm of participation culture that is prevalent on the internet and in society. By looking at memes as a socially constructed and intertextual discourse which represents different voices, perspectives, and creative insights, these cultural units are also a reflection of how cybercommunities think about, circulate, and imbue content with meaning in their everyday lives. Among many varieties of meme categories, music plays an important role in the production and consolidation of this online dimension, especially on YouTube and other social media. From rock to classical music, most music genres are featured either in static or audiovisual memes, except for one (large) period of music that is commonly referred to as 'modern' music. Despite niche and specialised meme pages, groups and forums related to contemporary music, this broad category is quite overlooked by YouTube compilations, social media featuring classical music, and other online spaces, thus mixing and confusing repertoires and stereotypes. With recurrent tropes regarding gender, power, and aesthetics that can be found either in pages dedicated to western contemporary art music and on other generalised platforms labelling it as 'ugly', 'male' or 'white', this paper aims to examine how the musical dimension affects the production of music memes and related online content, thus analysing its role in popular culture today and how cybercommunities—with or without audiovisual literacy—relate to and spread this (musical) phenomenon.